Cost of malaria treatment and health seeking behaviour of children under-five years in the Upper West Region of Ghana - Dalaba, Maxwell Ayindenaba (PLoS One, 2018)
BACKGROUND: There is limited knowledge on cost of treating malaria in children under-five years in northern Ghana which poses a challenge in determining whether interventions such as the National Health Insurance Scheme (NHIS) and Community-based Health Planning and Services (CHPS) have reduced the economic burden of malaria to households or not. This study examined the malaria care seeking and cost of treatment in children under-five years in the Upper West Region of Ghana. METHODS: The study used a cross-sectional, quantitative design and data were collected between July and August 2016 in three districts in the Upper West Region of Ghana. A total of 574 women who had under-five children were interviewed. Socio-demographic characteristics of respondents, malaria seeking patterns for under-five children with malaria as well as direct medical and non-medical costs associated with treating under-five children with malaria were collected from the patient perspective. Analysis was performed using STATA 12. RESULTS: Out of 574 women visited, about 63% (360) had children who had malaria and sought treatment. Most treatment was done at formal health facilities such as the health centres (37%) and the CHPS (35%) while 3% had self-treatment at home. The main reason for choice of place of treatment outside home was nearness to home (53%). The average direct medical and non-medical costs associated with treating an under-five child with malaria were US$4.13 and US$3.04 respectively. The average cost on transportation alone was US$2.64. Overall, the average direct medical and non-medical cost associated with treating an under-five child with malaria was US$4.91(range: minimum = US$0.13 –maximum = US$46.75). Children who were enrolled into the NHIS paid an average amount of US$4.76 compared with US$5.88 for those not enrolled, though the difference was not statistically significant (p-value = 0.15). CONCLUSIONS: The average cost to households in treating an under-five child with malaria was US$4.91. This amount is considerably high given the poverty level in the area. Children not insured paid a little over one US dollar for malaria treatment compared to those insured. Efforts to improve enrolment into the NHIS may be needed to reduce the cost of malaria treatment to households. Construction of more health facilities near to community members and at hard to reach areas will improve access to health care and reduce direct non-medical cost such as transportation costs.